SINERGITAS KEPOLISIAN DAERAH RIAU DENGAN BADAN NASIONAL PENANGGULANGAN TERORISME DALAM MENCEGAH DAN PENANGGULANGAN TINDAK PIDANA TERORISME - Gunggy Aulia; Dessy Artina; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Terrorism is also an international crime that poses a danger to security,world peace, and detrimental to the welfare of the community, so that eradicationneeds to be done in a planned and sustainable manner so that the human rights ofmany people can be protected and upheld. Prevention and prevention of terrorismis not only done by the Police but also all agencies and institutions related toterrorism, so in connection with this there needs to be cooperation between theNational Counterterrorism Agency (hereinafter abbreviated BNPT) and thePolice where both have roles and functions each in the prevention and control ofterrorism.This type of research is a sociological juridical research that is researchconducted by carrying out legal identification and how the effectiveness of theimplementation of that law applies in society. While the population and sampleare the whole parties related to the problems examined in this study, the source ofthe data used, primary data, secondary data and tertiary data, data collectiontechniques in this study with interviews and literature studies.From the results of the research problem there are two main things thatcan be revealed. First The most important thing from the prevention anderadication of terrorism crime is the need for good synergy between the RiauRegional Police and the National Counterterrorism Agency, as law enforcementofficers can carry out their duties and authority in accordance with the rules theyhave. Second, there are 2 factors faced in upholding criminal acts of terrorism,namely internal and external factors, internal factors themselves include the lackof maximum cross-sectoral cooperation between the Riau Regional Police and theNational Counterterrorism Agency with all government agencies, communityleaders, traditional leaders, as well as religious leaders, the absence ofrepresentatives of the National Counterterrorism Agency in the regions thatmakes coordination and monitoring of terrorism networks not optimal.Keywords: Terrorism - Preventing and Countering - Criminal Acts of Terrorism